Community Based Mitigation - Delita, Fitra (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Sinabung has erupted several times over the past few days spewing massive clouds of superheated gas and ash in to the sky and down its slopes in deadly pyroclastic flows. It’s dangerous or high risk for the local residents if the Mount Sinabung continuing eruption and will be threat thousands of people who live around the slopes. The main objectives of this research are to indentify history eruption of Mount Sinabung, to describe relocation area for refugees and to obtain information about community based mitigation in the case of Sinabung. This research uses qualitative research methods, where primary data is obtained through observation and semi-structured interviews and secondary data is obtained from literature and agencies data. The result showed that there are no confirmed historic eruptions before the re-awakening in August 2010 after 400 years dormancy, it has had activity in around 1600, recent documented events include an eruption in August 2010 ; September and November 2013; January, February and October 2014; June 2015; May 2016 and January, February, August 2017. Many of refugees have been relocated to several relocation area such as Siosar and Simpang Empat Subdistrict. The local residents around Sinabung had litle experience in dealing with its activity because there is litle information in terms of historical precedents. These are caused the vulnerabilities and risk of Mount Sinabung eruption is high. Community Based Tourism is the best strategy to reduce vulnerabilities and minimize human suffering in the case of Sinabung.